MARRIAGE EDUCATION PRACTICES AT RECONCILIATION SCHOOLS - Hadiyansyah, Dhuha; Hunaida, Wiwin Luqna; An’asy, Zaharil (JKKP (Jurnal Kesejahteraan Keluarga dan Pendidikan), 2024)
Abstract This study explores community-based marital education practices implemented by the Reconciliation School (SR), an initiative designed to help individuals heal emotional wounds caused by dysfunctional family systems. Employing a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis. The SR program adopts therapeutic frameworks developed by John Bradshaw and Virginia Satir, emphasizing family systems theory, inner child healing, and identity reconstruction. Data analysis was conducted using thematic coding and triangulation to ensure validity. Findings reveal significant improvements in participants’ interpersonal relationships and self-perception after completing the program. Participants reported enhanced emotional awareness, improved communication skills, and greater resilience in managing family dynamics. These results underscore the potential of community-based marriage education as a strategic alternative for strengthening family systems in Indonesia, particularly amid rising divorce rates, which currently range between 15–20 percent annually. Furthermore, SR’s hybrid model—integrating psychotherapy principles, adult learning theory, and spiritual reflection—creates a safe and transformative space for personal growth without requiring formal clinical intervention. The study recommends scaling similar programs through policy support and cross-sector collaboration to broaden accessibility. Ultimately, community-based family education offers a preventive approach to mitigating family dysfunction and its social consequences, fostering healthier relationships and sustainable family well-being. Abstrak Penelitian ini mengkaji praktik pendidikan perkawinan berbasis komunitas yang dilaksanakan oleh Sekolah Rekonsiliasi (SR), sebuah inisiatif yang bertujuan membantu individu memulihkan luka emosional akibat keluarga disfungsional. Studi ini menggunakan pendekatan kualitatif dengan metode studi kasus melalui wawancara mendalam, observasi, dan analisis dokumen. Program SR mengadopsi metode terapeutik dari John Bradshaw dan Virginia Satir yang menekankan pemahaman sistem keluarga, penyembuhan luka batin, serta penguatan identitas diri. Analisis data dilakukan melalui pengkodean tematik dan triangulasi untuk menjamin validitas. Hasil penelitian menunjukkan adanya perubahan positif pada hubungan interpersonal dan persepsi diri peserta setelah mengikuti program. Peserta melaporkan peningkatan kesadaran diri, kemampuan mengelola emosi, serta keterampilan membangun komunikasi yang sehat dalam keluarga. Temuan ini menegaskan bahwa pendidikan perkawinan berbasis komunitas dapat menjadi alternatif strategis untuk memperkuat sistem keluarga di Indonesia, khususnya di tengah meningkatnya angka perceraian yang mencapai 15–20 persen per tahun. Selain itu, model SR yang mengintegrasikan pendekatan psikoterapi, pembelajaran orang dewasa, dan refleksi spiritual menunjukkan efektivitas dalam menciptakan ruang aman bagi proses transformasi personal. Penelitian ini merekomendasikan pengembangan program serupa dengan dukungan kebijakan dan kolaborasi lintas sektor agar dapat menjangkau lebih banyak masyarakat. Dengan demikian, pendidikan keluarga berbasis komunitas berpotensi menjadi solusi preventif terhadap disfungsi keluarga dan dampak sosial yang ditimbulkannya.